Question of difficult life situations take-over - Kashcheeva A. V., Zimina I. V. (Scientific studies from theory to practice, 2016)
in this article the author gives a definition of "difficult life situation". The researchers examined the process of experiencing of situations requiring quick decision-making and changed behavior strategies, depending on their psychological significance for the individual.
Keywords: трудная жизненная ситуация; совладание; difficult life situation; take-over